Morphological evaluation of the effectiveness of the “Icon” resin infiltration method in acute and chronic superficial dental caries - N. O. Gevkaliuk; Y. L. Bandrivsky; M. Y. Pynda; V. Y. Pudiak; V. Y. Krupei; A. Y. Karnkivskyi (Regulatory Mechanisms in Biosystems, 2024)
The article presents the results of electron microscopy of 52 teeth with acute and chronic initial caries infiltrated with “Icon” material (DMG, Germany). According to the results of the study, in acute initial dental caries (white spot stage), the infiltrate filled almost the entire volume of the pathological focus (81.8 ± 6.7% of cases). The technique of infiltration by replacing the lost mineral with a low-viscosity light-curing resin creates a barrier inside the carious lesion. Minimally invasive approaches, including the enamel infiltration technique, can be used for caries in the white spot stage for therapeutic-prophylactic purposes. However, in the case of chronic initial caries (pigmented spot stage), the infiltrate does not infiltrate the entire depth of the lesion. In 79.0 ± 9.4% of the teeth of this group, non-infiltrated areas of carious lesions were localized within the surface layers of dentin. Extrapolating the results obtained to the clinic, we can assume that the infiltration of initial caries at the stage of a pigmented spot does not ensure the stabilization of the carious process. Clinical recommendation of the low-viscosity resin infiltration technique requires evidence that requires long-term clinical observations.